2023
DOI: 10.21468/scipostphys.14.6.152
|View full text |Cite
|
Sign up to set email alerts
|

Topological and quantum critical properties of the interacting Majorana chain model

Abstract: We study Majorana chain with the shortest possible interaction term and in the presence of hopping alternation. When formulated in terms of spins the model corresponds to the transverse field Ising model with nearest-neighbor transverse and next-nearest-neighbor longitudinal repulsion. The phase diagram obtained with extensive DMRG simulations is very rich and contains six phases. Four gapped phases include paramagnetic, period-2 with broken translation symmetry, \mathbb{Z}_2ℤ2 with broken parity symmetry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…In the Luttinger spin-liquid phase, the transverse correlation function should decay according to a power law G(r) ∝ 1/r 1/2K due to its critical nature [1,47]. The Luttinger parameter K determines the existence of Tomonaga-Luttinger spin liquid regime for specific values at the interval 1 < K < 2 [48,49]. The transverse spin-spin correlation within the DMRG method implementing MPS is straightforwardly calculated as a mean value of the product of the relevant raising and lowering spin operators.…”
Section: Phase Diagram and Scaling Behavior Of Vbs Transitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Luttinger spin-liquid phase, the transverse correlation function should decay according to a power law G(r) ∝ 1/r 1/2K due to its critical nature [1,47]. The Luttinger parameter K determines the existence of Tomonaga-Luttinger spin liquid regime for specific values at the interval 1 < K < 2 [48,49]. The transverse spin-spin correlation within the DMRG method implementing MPS is straightforwardly calculated as a mean value of the product of the relevant raising and lowering spin operators.…”
Section: Phase Diagram and Scaling Behavior Of Vbs Transitionsmentioning
confidence: 99%
“…implemented to identify and characterize the Luttinger regime in the hard-core Bose model with three-body interactions [48] and interacting Majorana chains [49].…”
Section: Phase Diagram and Scaling Behavior Of Vbs Transitionsmentioning
confidence: 99%
“…At the same time, and quite logically since fermions experience a repulsion, theoretical studies of Majorana chains are centered on extended models incorporating interactions between Majorana fermions in various forms [17][18][19][20][21][22][23][24][25][26]. In this paper we study the combined effect of the two interaction terms of the shortest possible range.…”
Section: Introductionmentioning
confidence: 99%
“…The Majorana chain with h = t = 1 and g interaction only has been intensely studied in recent years [18,19,26,33]. It was shown that for small coupling g the system remains in the critical Ising phase, however, at g ≈ 0.29 it undergoes a Lifshitz transition into a critical phase with the central charge c = 3 2 [19,26]. This phase is the Ising critical phase (c = 1 2 ) superposed with the floating phase, Luttinger liquid phase (c = 1), with incommensurate correlations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation